Application of Sujok Complementary Alternative Therapy to Reduce Pain Scale Levels in Patients with Heel Pain - Harahap, Maryam Latifah; Suryani, Elvi; Siregar, Rahmah Juliani (IJCS: International Journal of Community Service, 2024)
Heel Pain is pain at the bottom, back, or inside of the heel due to musculoskeletal disorders or specific conditions. One of the complementary alternative therapies that can be used to reduce the pain scale of Patients with heel pain are using Sujok therapy. Providing Sujok therapy is part of the integration of teaching and community service activities carried out by students and lecturers in Nursing at the Faculty of Medicine, Public Health and Nursing, Gadjah Mada University. Two patients with heel pain problems provided with Sujok therapy using a massage method with a probes in the hand which is a basic correspondence system. After that, fenugreek seeds were placed on the painful points that have been massaged previously. The pain scale was measured before and after therapy. It was found that the pain decreased from scale 7 to scale 5 in the first patient and scale 5 to scale 3 in the second patient. The conclusion from the results of community service activities shows that Sujok therapy uses a massage method on basic correspondence system and also attaching fenugreek seeds can be an effective alternatives complementary therapy for reducing the levels of pain scale in patients with heel pain.